The Uniqueness of Family Firms - Harijono Harijono (Universitas Multimedia Nusantara, 2010)
This study focuses on family business theory from two theories of the firm perspectives: the incomplete contract and the agency perspectives. It shows that families represent a special class of large shareholders that potentially have a unique incentive structure and power in the firm. The unique characteristics of family firms potentially make their performance and their corporate decisions making different from those of non-family firms. The empirical evidences tend to support this argument. However, further quantitative and qualitative research to establish the relations between family control and several aspects of corporate decision making in different institutional and cultural settings remains to be done. Keywords: Agency, Control, Cultural, Family Business, Investment, Shareholders